The Dasytidae (Coleoptera) of Sardinia - Liberti, Gianfranco (Zootaxa, 2009)
The study of over 10,000 specimens of Dasytidae from about 35 collections has led to the conclusion that 8 genera and 32 species and subspecies of this family, all actually observed by the author, occur in Sardinia. This number is believed to be rather close to completion. A further 30 species, reported in the past as occurring on the island, are discussed and have been removed from the list. Identification keys based on external characters only are proposed for genera and species. However, for difficult groups and where confusion may arise, drawings of aedeagi are supplied. An annoted cataloguefollows with, for each species, synonymies, bibliography, a list of sampling localities with last year of collection, notes, and chorotype. A zoogeographical analysis shows that the Sardinian Dasytidae conform to a Central Mediterranean type, with rather strong North African influences and with a high presence of strict endemics (11 species), higher than in Corsica (7 species). Danacea (Allodanacaea) is no doubt the most interesting group with 7 taxa, none of which are spread all over Sardinia and 2 of which—D. (A.) gorditana Liberti and D. (A.) nympha Liberti—only occur in a tiny area in the Nurra region. Two species, Dasytes doderoi Pic and Aplocnemus (Diplambe) januaventi Liberti, both strict Sardinian endemics, are very rare and poorly known: the first is only known on two female specimens, both collected in the Gennargentu area many years ago; the second seems in a “safer” situation because several specimens have been collected recently. Trap samples (mainly Malaise) from the Marganai and Montimannu region-owned forests (SW Sardinia, respectively Carbonia-Iglesias and Medio Campidano provinces), are also discussed.